Evaluation Of The Rationality Of The Use Of Anemia Drugs In Anemia Patients In Rsd Gunung Jati Cirebon City For The Period January-December 2022 - Miftahul Janah; Like Efriani; Teguh Adiyas Putra (Jurnal EduHealth, 2023)
Anemia is a condition where the hemoglobin (Hb) level in the blood is less than normal levels. The aim of this research is to determine the characteristics of anemia patients in the inpatient installation at RSD Gunung Jati, Cirebon City, to find out the prescribing of anemia at RSD Gunung Jati, Cirebon City for the period January- December 2022 and to determine the rationality evaluation of the use of anemia medication at RSD Gunung Jati, Cirebon City on an appropriate basis. indication, correct diagnosis, right drug and right dose. This study used a retrospective research design. The rationality analysis was carried out using a purposive sampling method. The data taken is medical record data and patient prescriptions to see the rationality of treatment. The number of samples in this study was 73 samples which met the inclusion criteria. The statistical analysis used in this research is chi-square and Mann-Whitney. The parameters used in the research are the correct indication, correct diagnosis, correct drug and correct dose. The results of the study showed that anemia was mostly experienced by women as many as 37 patients (51%) and elderly people (46-65 years) as many as 40 patients (55%) with elementary school education levels as many as 35 patients (48%). The anemia drugs most commonly used by anemia patients in patient installations at RSD Gunung Jati, Cirebon City for the period January-December 2022 are multivitamins, haemostatics, neurotropic vitamins and iron preparations, respectively. The evaluation results showed that the indication was 100% correct, the diagnosis was 100% correct, the drug was 100% correct and the dose was 95% correct. The statistical test results showed that the use of anemia drugs in anemia patients met the rational requirements and had a significant rationality value.